THE EFFECT OF SELF EFFICACY AND PEER CONFORMITY ON CHEATING BEHAVIOR OF STUDENT ACCOUNTING SMK NEGERI IN JAKARTA - Fadillah, Rahmi; Zulaihati, Sri; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to measure the self efficacy and peer conformity of the cheating behavior of accounting students of SMK Negeri in Jakarta using survey methods. The population in this study was one of SMK Negeri in Jakarta, with 10 and 11 class accounting sample students evaluating 108 students. The sampling technique uses proportional random sampling. Based on the results of the study concluded about self efficacy and peer conformity have a simultaneous relationship to cheating relationships. Adjusting to a large extent influences cheating relationships, while peer conformity influences cheating behavior.